MANAJEMAN WAKTU BELAJAR SISWA BERPRESTASI KELAS V SD DI LINGKUNGAN RT 005/04 PULAU TIDUNG - Perdiansyah Perdiansyah; Slamet Widodo (Journal of Professional Elementary Education, 2022)
This study aims to describe the management of learning time for outstanding students in fifth grade elementary school in RT 005/04 Tidung Island, South Thousand Islands. The research method used in this research is descriptive qualitative research method. The selection of the sample in this study used a purposive sampling technique, where the researcher chose a sample with certain considerations. The samples used in this study were 2 high achieving fifth grade students who were in the RT 005/04 Tidung Island, South Thousand Islands. The data collection techniques used are questionnaires or questionnaires and structured interviews. Meanwhile, the data analysis used the Miles and Huberman model analysis technique. The results of this study are, students who have good achievements have good time management such as having good short-term study plans, having a wise attitude in spending time, and having good long-term study plans, and getting very good support from his parents